Development and Performance Enhancement of MEMS Helix Antenna for THz Applications using 3D HFSS-based Efficient Electromagnetic Optimization - Abdelhakim Boudkhil; Mohammed Chetloul; Nadia Benabdellah; Nasreddine Benahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Interest of Micro-Electromechanical System (MEMS) antennas in Terahertz (THz) applications has rapidly expanded in recent years due to the advent of accurate Computer Aided Design (CAD) tools. The very special needs of newly proposed MEMS antennas, especially with a wide bandwidth range, require advanced optimization procedures of enhancing already established designs. This paper provides a compact design of a wideband MEMS helix antenna optimized using tree-dimensional High Frequency Structure Simulator (3D-HFSS) based on Quasi-Newton (Q-N) and Sequential Non Linear Programming (SNLP) techniques to modify the antenna structure with a high accuracy for the selective band of frequencies by training the samples and minimizing the error from Finite Element Method- (FEM) based simulation tool. The helix antenna is presented using MEMS technology and shows high performance demonstrated by very low return losses of less than -20 to -65 dB for a wide range of frequencies from 2.5 to 5 THz. High antenna geometry precision and efficient performance are finally achieved by rectifying and synthesizing various tunable parameters embedded in silicon substrate including both helix form and feeding line parameters.